Asymptomatic Massive Fibrous Dysplasia Obliterating Maxillary Sinus Extending to the Skull Base: a Case Report and Review of Literature - Sigdel, Brihaspati; Neupane, Bhima; Pokhrel, Amrit; Kshetri, Bikash; Sharma, Keshab; Ghimire, Ashish; Jha, Avinash (Journal of College of Medical Sciences-Nepal, 2022)
Fibrous dysplasia is a rare bone condition in which normal bone is replaced by aberrant fibrous tissue. The patient may come to evaluate with other diseases and while doing investigations, it is observed. Here we present a case of 24 years male with fibrous dysplasia who came to our OPD with swelling around the left cheek region for 5 days. The patient underwent a Computerised tomography scan which revealed an expansile, sclerotic, cystic ground-glass appearance that extended to the maxillo-alveolar ridge, right sphenoid sinus wall, right pterygoid plate, and zygomaticofacial suture. The right maxillary sinus was almost obliterated. These radiographical features of the lesion were indicative of fibrous dysplasia in the maxilla.